Vitrified embryo transfer in Merino sheep under extensive conditions - Gibbons, Alejandro Eduardo; Bruno Galarraga, Maria Macarena; Fernandez, Jimena; Gonzalez Bulnes, Antonio; Cueto, Marcela Isabel (Brazilian College of Animal Reproduction, 2019)
The aim was to evaluate pregnancy success after transfer of embryos vitrified in micropipette tips in Merino sheep under extensive conditions. A second objective was to evaluate the influence of embryo stage in such pregnancy rate. One hundred and twenty-seven embryos were rewarmed and transferred into recipient ewes. On rewarming, the embryos were placed into three-step cryoprotectant dilutions. Finally, prior to transfer to recipient females, embryos were maintained in Basic Medium for 5 min at 25ºC and were re-evaluated by morphological criteria; all degenerated embryos were eliminated. Recipient ewes (n = 150) were treated for estrus with sponges placed for 14 days and 300 IU of eCG. At embryo transfer, three experimental groups were defined: morulae transferred on Day 7, blastocysts transferred on Day 7 and blastocysts transferred on Day 8 after sponge removal. In all groups, semi-laparoscopic transfer of one rewarmed embryo per recipient was performed. Pregnancy was diagnosed by ultrasonography on day 28 after embryo transfer. The embryo selection rate after rewarming was higher for blastocysts (89.3% - 67/75) compared to morulae (65.9% - 60/91) (P < 0.05). Pregnancy diagnosis showed a 38.3% (23/60) of success after morula transfer on Day 7 post progestagen removal. The day of transfer showed a significant influence on pregnancy rate after blastocyst transfer (Day 8, 55.9% - 19/34 vs Day 7, 21.2% - 7/33) (P < 0.05). Blastocysts transfer on Day 8 showed the highest global efficiency (pregnancies/total embryos after rewarming) (47.5% - 19/40) (P < 0.05). In conclusion, reproductive efficiency obtained by vitrified embryo transfer allows its recommendation for embryo transfer programs under extensive conditions. The importance of considering the synchrony between the embryo age and the recipient uterus stage is emphasized.